Diurnal variation of cloudiness during southwest monsoon season using I NSAT-IB radiance data - RAO , A. V. R. K.; RAO, V. R (MAUSAM, 1993)
An attempt has been made to study the diurnal variation of convective clouds. For this study 3 hourly full resolution infrared data of INSAT-IB have been used for the monsoon season (Jun-Sep) of 1987-89. The area of study extends from 35°N to 25°S and 40oE to l00oE, which is subdivided into small areas of 2.5x 2.5 Lat./Long. Mean temperature and the fractional area covered by clouds colder than a given threshold temperature over each sub area are the parameters used for this study. Two threshold temperatures. namely 265°K & 235oK are chosen to represent convective clouds and deep convective clouds respectively. Using the three hourly observations, times of maximum and minimum convective activity are also obtained. Maximum convective activity is observed over head Bay of Bengal at about noon and this maximum migrates westward onto land till midnight and swings back to oceanic area by morning. This eastwest oscillation is less over equatorial regions (open ocean).